Contrasting policy advisory systems for the energy transition: A comparative study of Portugal and Denmark - Vegi da Conceição, M.; Asensio, M.; Vala, F. (Frontiers in Political Science, 2026)
Achieving climate goals requires robust systems for organizing policy advice. This paper investigates how Policy Advisory Systems (PAS) for renewable energy are structured in Portugal and Denmark. Using a qualitative comparative case study, the research analyses four PAS dimensions: declining state analytical capacity, politicization, externalization, and corporate capture. Findings reveal contrasting models: Portugal's centralized, politicized system vs. Denmark's institutionalized, participatory one. In addition, the study includes an in-depth analysis of the development of renewable energy communities in Portugal to examine how policy advisory dynamics operate in practice. The paper contributes to comparative public policy theory by demonstrating how sector-specific advisory structures reflect broader administrative traditions and influence the integration of energy justice and citizenship into policy outcomes.